2022
DOI: 10.30574/gscbps.2022.21.2.0428
|View full text |Cite
|
Sign up to set email alerts
|

A review of hot melt extrusion paired fused deposition modeling three-dimensional printing for developing patient centric dosage forms

Abstract: In recent years, the demand for developing patient-centric dosage forms is increasing enormously with the increasing patient population. Much research is ongoing exploring various additive manufacturing techniques for developing pharmaceutical medications. Poor solubility of drug substances and underdeveloped manufacturing strategies are majorly affecting the pharmaceutical industry's revenue. Developing intravenous dosage forms for drug substances with poor solubility will affect the revenue of the pharmaceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…In vivo studies have shown that these factors are critical for determining the success of oral formulations, so understanding their intricate workings is fundamental to improving results. Through careful analysis in vitro, researchers can gain insight into how they might be able to improve those rates and thus ultimately enhance the efficacy of such treatments [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have shown that these factors are critical for determining the success of oral formulations, so understanding their intricate workings is fundamental to improving results. Through careful analysis in vitro, researchers can gain insight into how they might be able to improve those rates and thus ultimately enhance the efficacy of such treatments [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…This lag time also involves a manual intervention to remove the printed dosage forms and then start a second print. This practical limitation is majorly due to the confined print bed area of most FDM 3D printers, which also limits the applicability to a personalized on-demand application [ 15 , 16 , 17 ]. Furthermore, the involvement of a manual intervention followed by post-processing steps and collection makes it unfavorable for scaling up and bringing the printed dosage forms to the market [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%